The codebreaker's secret [large type] - Ackerman, Sara (Center Point Large Print, 2022)
"1943. As war in the Pacific rages on, Isabel Cooper and her codebreaker colleagues huddle in the dungeon at Station Hypo in Pearl Harbor, deciphering secrets plucked from the airwaves in a race to bring down the enemy. Isabel has only one wish: to avenge her brother's death. But she soon finds life has other plans when she meets his best friend, a hotshot pilot with secrets of his own. 1965. Fledgling journalist Lu Freitas comes home to Hawai'i to cover the grand opening of the glamorous Mauna Kea Beach Hotel, Rockefeller's newest and grandest project. When a high-profile guest goes missing, Lu forms an unlikely alliance with an intimidating veteran photographer to unravel the mystery. The two make a shocking discovery that stirs up memories and uncovers an explosive secret from the war days. A secret that only a codebreaker can crack."--